Reducing soil and leaf shadow interference in UAV imagery for cotton nitrogen monitoring - Yin, Caixia; Wang, Zhenyang; Lv, Xin; Qin, Shizhe; Ma, Lulu; Zhang, Ze; Tang, Qiuxiang (Frontiers in Plant Science, 2024)
The accuracy of monitoring cotton nitrogen content may be compromised in drone imagery, where individual leaves can be shadowed by others. To eliminate the interference of soil and leaf shadows on cotton spectral data and to reliably monitor cotton nitrogen content, it is essential to address these challenges. In this work, green light (550 nm) is divided into 10 levels to limit soil and leaf shadows (LS) on cotton spectrum. How many shadow has an influence on cotton spectra may be determined by the strong correlation between the vegetation index (VI) and leaf nitrogen content (LNC). Several machine learning methods were utilized to predict LNC using less disturbed VI. R-Square (R 2 ), root mean square error (RMSE), and mean absolute error (MAE) were used to evaluate the performance of the model. The results showed that: (ⅰ)after the spectrum were preprocessed by gaussian filter (GF), SG smooth (SG), and combination of GF and SG (GF&SG), the significant relationship between VI and LNC was greatly improved, so the Standard deviation of datasets was also decreased greatly; (ii) the image pixels were classified twice sequentially. Following the first classification, the influence of soil on vegetation index (VI) decreased. Following secondary classification, the influence of soil and LS to VI can be minimized. The relationship between the VI and LNC had improved significantly; (ⅲ) After classifying the image pixels, the VI of 2-3, 2-4, and 2-5 have a stronger relationship with LNC accordingly. Correlation coefficients(r) can reach to 0.5. That optimizes monitoring performance when combined with GF&SG to predict LNC, support vector machine regression (SVMR) has the better performance, R 2 , RMSE, and MAE up to 0.86, 1.01, and 0.71, respectively. The UAV image classification technique in this study can minimize the negative effects of soil and LS on cotton spectrum, allowing for efficient and timely predict LNC.